Scenarios and key performance indicators: an application to the future of healthcare provision in Portugal - Jesus, Margarida Breia de (2021)
The present Work Project has the ambition to assessthe relationship between Scenario Planning and Key Performance Indicators(KPIs). In order to test theresearch hypothesis that “Different scenarios require different Key Performance Indicatorsto monitor organization’s performance”,a questionnaire and aworkshop to Hospital Administrators from Centro Hospitalar e Universitário deCoimbrawere performed.The results revealednot merelythat, in fact, different scenarios require different KPIs, but also that scenarios may be a relevant tool tosurpass some prominent challenges related to KPIssuch as the poor alignment of the indicators with the organization’s objectives and the absence of forward-looking metricsin organizations.